2015
DOI: 10.1007/s00542-015-2634-0
|View full text |Cite
|
Sign up to set email alerts
|

A flexible multimodal tactile display array for virtual shape and texture

Abstract: User study results showed that the fabricated multimodal tactile display system successfully delivered both shape information with an accuracy of 73 % and texture information with an accuracy of 90 %. This work demonstrates the potential of our multimodal tactile display system for uses in various applications such as tele-operation, tactile communication, and visual presentation for visually impaired.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…There are many examples of haptic devices using soft lithography and molding techniques . For example, Son et al demonstrated a flexible tactile display based on molding technique using PDMS . They formed a number of pneumatic microchannels in a PDMS layer.…”
Section: Fabrication Methods For Emerging Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many examples of haptic devices using soft lithography and molding techniques . For example, Son et al demonstrated a flexible tactile display based on molding technique using PDMS . They formed a number of pneumatic microchannels in a PDMS layer.…”
Section: Fabrication Methods For Emerging Materialsmentioning
confidence: 99%
“…In another example, Son et al developed a multimodal flexible tactile display for teleoperation applications . A combination of pneumatic and electromagnetic forces was used to actuate the display.…”
Section: Tactile Displays Based On Emerging Materialsmentioning
confidence: 99%
“…[ 190 ] Emerging materials include soft materials (e.g., gel, [ 191 ] liquid and rubber [ 192 ] ), organic materials, [ 193 ] and nanomaterials (e.g., graphene [ 194 ] and CNTs [ 195 ] ), and composites. [ 196 ] Based on the working principles, soft actuators can be classified into pneumatic actuators, [ 197 ] electroactive polymer actuators, [ 198 ] electrostatic force actuators, [ 199 ] electromagnetic actuators, [ 200 ] fluidic actuators, [ 201 ] and liquid crystal elastomeric actuators. [ 202 ]…”
Section: Outputmentioning
confidence: 99%
“…Moreover, the advantages of FPCB, such as strong heat resistance, rust resistance, water resistance, and chemical resistance, are directly inherited by our actuator. FPCBs are widely being utilized to interface with microactuators and circuits [18][19][20][21][22][23]. It has also been demonstrated that FPCB is able to generate motion when combined with external electrodes [24,25].…”
Section: Introductionmentioning
confidence: 99%